Indonesian Salafi Education: Change and Sustainability Attitudes toward Ideology in PPIM al-Mukmin Ngruki - Nugroho, Taufik; Rahman, Arif; Al-Makky, Akrom Ridwan Ali; Surur, Misbahul (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2025)
This study examines the changing and sustaining ideological attitudes within PPIM Al-Mukmin Ngruki. The central research question is: How has the conservative PPIM Ngruki changed and sustained its attitude toward ideology? This qualitative study draws upon primary sources, including interviews with administrators and founders of PPIM, as well as official government and institutional documents. Secondary sources include dissertations, theses, journal articles, organizational statutes (AD/ART), and key instructional texts used by PPIM Ngruki. Findings reveal that the ideological transformation of Al-Mukmin Ngruki’s conservative community was driven by two key factors: (1) strong external pressure and negative stigma from both the government and the wider public, who viewed PPIM Ngruki as a hardline Islamic boarding school; and (2) an internal process of self-evaluation regarding their understanding of Islam and their attitudes toward Pancasila and the Unitary State of the Republic of Indonesia (NKRI). Consequently, PPIM Ngruki’s ideological stance shifted from a conflictual–contestational mindset to an accommodative–inclusive orientation as part of its sustainability effort.